2012
DOI: 10.1105/tpc.111.094417
|View full text |Cite
|
Sign up to set email alerts
|

Operon flv4-flv2 Provides Cyanobacterial Photosystem II with Flexibility of Electron Transfer

Abstract: Synechocystis sp PCC 6803 has four genes encoding flavodiiron proteins (FDPs; Flv1 to Flv4). Here, we investigated the flv4-flv2 operon encoding the Flv4, Sll0218, and Flv2 proteins, which are strongly expressed under low inorganic carbon conditions (i.e., air level of CO 2 ) but become repressed at elevated CO 2 conditions. Different from FDP homodimers in anaerobic microbes, Synechocystis Flv2 and Flv4 form a heterodimer. It is located in cytoplasm but also has a high affinity to membrane in the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
174
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 131 publications
(192 citation statements)
references
References 88 publications
(106 reference statements)
13
174
0
Order By: Relevance
“…The results revealed that the absence of Flv2 and Flv4 causes slower Q A 2 oxidation compared with the wild type ( Fig. 9; Zhang et al, 2012). In line with these results, Q A 2 reoxidation was shown to be significantly faster in the flv4-2/OE mutant compared with the wild type, especially compared with DpsbA2 (Fig.…”
Section: Psii Properties In Flv Mutantssupporting
confidence: 78%
See 2 more Smart Citations
“…The results revealed that the absence of Flv2 and Flv4 causes slower Q A 2 oxidation compared with the wild type ( Fig. 9; Zhang et al, 2012). In line with these results, Q A 2 reoxidation was shown to be significantly faster in the flv4-2/OE mutant compared with the wild type, especially compared with DpsbA2 (Fig.…”
Section: Psii Properties In Flv Mutantssupporting
confidence: 78%
“…In addition, the experiments were also performed with the Dflv4 mutant, which does not express the Flv4, Sll0218, and Flv2 proteins ( Fig. 1B; Zhang et al, 2012). The latter mutant contained the kanamycin cassette in sll0217 (flv4), the first gene of the operon .…”
Section: Overexpression Of the Flv4-2 Operon In Synechocystismentioning
confidence: 99%
See 1 more Smart Citation
“…This was further supported by investigations in Synechococcus, in which deletion of COX and COX/ARTO resulted in 1.7-and 2.2-fold increases, respectively, in the reduction rate of PSI (Nomura et al, 2006). Alternative electron sinks, such as the Flv2/Flv4 complex, which accepts electrons directly from PSII (Zhang et al, 2012), the hydrogenase complex, nitrate reductase, or carbon fixation, may compensate for the loss of terminal oxidase activity, as demonstrated by increased hydrogen production in a Synechocystis COX/Cyd-deficient strain (Gutthann et al, 2007). Energization of both the thylakoid and cytoplasmic membrane electron transfer chains is important under conditions of salt stress in Synechocystis (Jeanjean et al, 1990(Jeanjean et al, , 1993Peschek et al, 1994) and Synechococcus sp.…”
mentioning
confidence: 49%
“…Another important difference in the photoprotection strategies of higher plants and cyanobacteria is a unique valve in the latter, composed of the Flv2/Flv4 heterodimer and the Sll0218 protein, which provides extra capacity for directing electrons away from PSII. The valve subunits accumulate under conditions that induce excess reduction of the ETC [46] that pose a potential hazard to the ETC and in particular to PSI.…”
Section: The Facts and Enigmas In Photoprotectionmentioning
confidence: 99%